Pengaruh Cahaya dan Wadah Penyimpanan terhadap Efektivitas Nuclear Polyhedrosis Virus dalam Mengendalikan Spodoptera litura - Anasta, Dinda Nadia; Rahmadhini, Noni (Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
Spodoptera litura pest attacks can cause disturbances in plant growth and lead to considerable yield losses. Control that is often done to control S. litura is usually with chemical insecticides, but excessive use of chemical insecticides has the potential to cause adverse effects on the environment. As a safer and more sustainable alternative, pest control can be done through the utilization of biological agents such as pathogens that function as bioinsecticides, one of which is Nuclear Polyhedrosis Virus (NPV). This research aims to analyze the effect of length of exposure to sunlight and the type of storage container on the effectiveness of NPV in controlling S. litura. NPV isolates were exposed to direct sunlight for 1, 3, 6 hours in glass and plastic vial containers. The isolate was infected to 3rd instar S. litura larvae using feed contamination technique. This research implemented a factorial Completely Randomized Design (CRD), with 6 treatments and control. The results showed that NPV isolates with MK.1 and MP.1 treatments were effective in producing a percentage of larvae mortality and were able to suppress the formation of pupae and imago with a mortality percentage of 84,2 % and 71,4 % at 72 hours after aplication. Length of sunlight exposure affects the effectiveness of NPV isolates.